REVIEW: THE INFLUENCE OF SERVICES BASED ON SHARIA PRINCIPLES ON PATIENT SATISFACTION IN THE PHARMACY UNIT OF KARANGDORO COMMUNITY HEALTH CENTER, SEMARANG CITY - Ramadhani, Nur Anisah; Ramadhani, Azmi; Yantiningrum, Dyah (SAINS INDONESIANA, 2025)
Puskesmas (Community Health Centers) are primary healthcare facilities that provide essential health services including promotive, preventive, curative, and rehabilitative efforts in a comprehensive, integrated, and continuous manner. This unified healthcare approach serves as a standard for all health facilities in Indonesia, including Puskesmas. Islamic-based health services are characterized by four core values: rabbaniyyah (God-centered), akhlaqiyyah (moral), waqi’iyyah (realistic), and insaniyyah (humanistic). This study aims to determine the influence of services based on Sharia principles on patient satisfaction in the Pharmacy Unit of Karangdoro Puskesmas, Semarang City. A descriptive quantitative  approach was used with purposive sampling. The results show that all instruments across the five dimensions (Rabbaniyyah, Akhlaqiyyah, Waqi’iyyah, Insaniyyah, and Satisfaction) are valid and reliable for data collection. Patients expressed high satisfaction with services that were polite, fair, friendly, and informative in accordance with Islamic values. However, statistical analysis (t-test and ANOVA) revealed that Sharia-based service principles did not have a significant effect on patient satisfaction, as all significance values were greater than 0.05. Although patients appreciated the Sharia approach, it has not been statistically proven to improve satisfaction. Therefore, enhancing patient satisfaction requires improving pharmacy services in a more comprehensive way, rather than focusing solely on religious values.